Dimethyl Fumarate Alleviates NLRP3 Inflammasome Activation in Microglia and Sickness Behavior in LPS-Challenged Mice - Tastan, Bora; Arioz, Burak I.; Tufekci, Kemal Ugur; Tarakcioglu, Emre; Gonul, Ceren Perihan; Genc, Kursad; Genc, Sermin (Frontiers in Immunology, 2021)
NLRP3 inflammasome activation contributes to several pathogenic conditions, including lipopolysaccharide-induced sickness behavior which is defined as attenuated mobility and depressive behaviors. Dimethyl fumarate is an immunomodulatory and anti-oxidative molecule commonly used in the symptomatic treatment of multiple sclerosis and psoriasis. We investigated the potential beneficial use of DMF on microglial NLRP3 inflammasome activation in vitro and in vivo. The N9 microglial cell line and 12–14 weeks-old male BALB/c mice were used to investigate DMF’s effects on microglial NLRP3 inflammasome activation. For in vitro study, LPS and ATP model was used to induce NLRP3 inflammasome activation. DMF’s effects on inflammasome markers, pyroptotic cell death, ROS formation, and Nrf2/NF-κB pathways were assessed. For in vivo study, mice were treated with LPS (5 mg/Kg), DMF (30 mg/Kg) + LPS and ML385 (30 mg/Kg) + DMF + LPS. Behavioral tests (open field, forced swim test, and tail suspension test) were carried out to see changes in lipopolysaccharide-induced sickness behavior. Furthermore, NLRP3 and Caspase-1 expression in isolated microglia were determined by immunostaining. Here we demonstrated that DMF ameliorated LPS and ATP-induced NLRP3 inflammasome activation by reducing IL-1β, IL-18, caspase-1, and NLRP3 levels, reactive oxygen species formation and damage, and inhibited pyroptotic cell death in N9 murine microglia via Nrf2/NF-κB pathways. DMF also improved lipopolysaccharide-induced sickness behavior in male mice and decreased caspase-1 and NLRP3 levels via the Nrf2 activation. Additionally, we showed that DMF pretreatment decreased miR-146a and miR-155 both in vivo and in vitro. Our results proved the effectiveness of DMF on the amelioration of microglial NLRP3 inflammasome activation. We anticipate that this study will provide valuable consideration for further studies aiming to inhibit NLRP3 inflammasome activation found in many diseases and a better understanding of its underlying mechanisms.